2013
DOI: 10.1111/1365-2745.12139
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for scale‐ and disturbance‐dependent trait assembly patterns in dry semi‐natural grasslands

Abstract: Summary1. The mechanisms driving nonrandom assembly patterns in plant communities have long been of interest in ecological research. Competing ecological theories predict that coexisting species may either be more functionally dissimilar than expected by chance (with functional 'divergence' mainly reflecting niche differentiation) or be functionally more similar than expected (with functional 'convergence' reflecting either the outcome of environmental filtering or weaker-competitor exclusion effects). Assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
131
5
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(162 citation statements)
references
References 41 publications
17
131
5
6
Order By: Relevance
“…However, consideration of ITV at the local (within-plot) scale yields additional information that may help understand how specific environmental factors drive community trait assembly (Albert et al 2010a, Jung et al 2010, Paine et al 2011, Siefert 2012. For instance, contrary to other studies on the role of spatial heterogeneity in promoting community trait divergence (e.g., de Bello et al 2013), our result shows that spatial heterogeneity of soil resources was not important in driving greater ITV among dominant species on the most productive islands. Further, ITV at local scales v www.esajournals.org may be an important (though largely neglected) element of community-level functional composition and diversity, and one that could potentially be an important driver of ecosystem processes such as primary productivity and nutrient cycling in the manner that has been shown for intraspecific variation at landscape scale (Garnier et al 2004).…”
Section: Discussioncontrasting
confidence: 86%
“…However, consideration of ITV at the local (within-plot) scale yields additional information that may help understand how specific environmental factors drive community trait assembly (Albert et al 2010a, Jung et al 2010, Paine et al 2011, Siefert 2012. For instance, contrary to other studies on the role of spatial heterogeneity in promoting community trait divergence (e.g., de Bello et al 2013), our result shows that spatial heterogeneity of soil resources was not important in driving greater ITV among dominant species on the most productive islands. Further, ITV at local scales v www.esajournals.org may be an important (though largely neglected) element of community-level functional composition and diversity, and one that could potentially be an important driver of ecosystem processes such as primary productivity and nutrient cycling in the manner that has been shown for intraspecific variation at landscape scale (Garnier et al 2004).…”
Section: Discussioncontrasting
confidence: 86%
“…dispersal limitation) at large spatial scale (landscape, km 2 >), while at more local scale (m 2 -km 2 ) deterministic processes are ruling species assemblage (Lortie et al 2004;Gravel et al 2006). In dry semi-natural grassland in south-western Sweden, this pattern was effectively observed among a series of leaf and whole-plant traits comparing landscape scales with patch scales (de Bello et al 2013). In addition, these authors observed for this series of traits clear patterns of convergence at a patch scale and divergence at a smaller spatial scale (neighborhood, cm 2 -m 2 ), Importance of a functional trait and b functional dissimilarity values to explain species abundance in three communities of six species.…”
Section: Which Assembly Process For Which Conditions?mentioning
confidence: 97%
“…However, both assembly processes can operate in a given community (Kraft et al, 2015), but their predominance is likely to vary with spatial scale and stress level, among other factors (Cavender-Bares et al, 2009;Spasojevic and Suding, 2012;de Bello et al, 2013;Laliberté et al, 2013). In our system, habitat filtering may have restricted species composition and functional divergence of communities, by species sorting, before interspecific interactions could limit the phylogenetic similarity between co-occurring species.…”
Section: Discussionmentioning
confidence: 94%
“…We propose two nonmutually exclusive explanations for this pattern. First, greater environmental heterogeneity generated by disturbance may allow functionally different species to occupy different microhabitats within a site, thus increasing overall functional divergence (de Bello et al, 2013;Kraft et al, 2015) and decreasing the degree of phylogenetic clustering, provided that life history traits show phylogenetic signal (Pausas and Verd u, 2010;de Bello et al, 2013). Actually, it has been shown that increased disturbance by fossorial mammals causes soil heterogeneity, because inter-mound microsites have higher cover of dominant species and different microclimatic conditions compared with mound microsites (Whitford and Kay, 1999).…”
Section: Discussionmentioning
confidence: 99%